Architectural Elements and the Serene Atmosphere of Jusuf Kalla Library, Universitas Islam Internasional Indonesia (UIII) - Irnawati, Yunia -; Pramantha, Raudina Qisthi (Universitas Syiah Kuala, 2024)
This study investigates the architectural atmosphere of the Jusuf Kalla Library, Universitas Islam Internasional Indonesia (UIII) emphasizing the design elements that contribute to shaping its spatial experience. The study employs a descriptive qualitative methodology, utilizing site writing method and direct observation as the primary data collection methods. The findings highlight several key architectural elements that collaboratively create an environment conducive to focused learning. These elements include material selection, color schemes, lighting design, spatial configuration, proportions, and sensory factors such as scent, sound, and air quality. The interplay of these elements establishes a tranquil and comfortable atmosphere that supports individual learning and concentration. The analysis indicates that the spatial design of the Jusuf Kalla Library is more oriented toward individual study spaces rather than group learning areas. This design choice intensifies the library's serene, contemplative atmosphere, which is particularly conducive to solitary learning. The architectural design of the Jusuf Kalla Library, through its careful attention to sensory and spatial elements, cultivates an environment that enhances the user experience by fostering a focused, serene, and intellectually stimulating setting.Keywords: Library Atmosphere, Architectural Deisgn, Sensory Experience, Ambience, Learning Space